Investigating Preservice Science Teacher Ethical Sensitivity through Computer Game and Video - Shawn Holmes; Leonard Annetta; Loni Crumb (Journal of Education in Science, Environment and Health)
A computer-based simulation, Hazelton High at REST (HHR), with embedded performance-based assessments and Likert-type survey questions was created to assess preservice teacher recognition of racial and gender intolerant behaviors. The simulation was modeled after the Racial Ethical Sensitivity Test (REST), a reliable video-based assessment, measuring professionals’ ethical sensitivity for cultural competence and recognition of intolerant behaviors in school settings. Ethical sensitivity skills, based on education professional ethics, are used to determine knowledge of ethical responsibility and professional attitudes and behaviors. A mixed-methods comparison study was conducted between HHR and the REST-video with 31 preservice science education students to investigate the effect of each on their ethical sensitivity. A post-simulation assessment was also conducted to determine and the usability and perception of HHR. It was hypothesized; HHR, an immersive simulation, would affect perspective taking of preservice science teachers and indirectly influence their ethical sensitivity. Data analysis determined ethical sensitivity score (EES) for HHR and REST-video using a survey and performance-based assessments. Post-simulation interview helped inform how a participant perceived the HHR. Results indicate the REST-video group had a significantly higher EES than the HHR group. Performance-based assessments within HHR showed a more comprehensive and complex picture of participant EES. The implication of this work for science education programs to use professional codes as a guide for evaluation and development of candidate disposition concerning cultural competency and the use of Serious Educational Games (SEGs) as ethical sensitivity assessments.